Integrating Realistic Mathematics Education With Islamic Values: A Statistics Module for Grade X Students - Isnawati, Ayus Riana; Hardianti, Indira Pusparani; Ardani, Riska Ayu (Universitas Teknokrat Indonesia, 2025)
The urgency of this research arises from the absence of a statistics module based on the RME approach that integrates Islamic values, designed to help students understand mathematics contextually while instilling character values. This research is development research using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model which aims to produce a high school statistical module based on the RME approach integrated with Islamic values that meets valid and practical criteria. The subjects of this research were class X of SMAN 4 Semarang's students. The data collection technique used was a validation and practicality questionnaire. The validity instrument consists of a validation sheet for material expert, media, Islamic and practitioner modules, as well as a practical instrument, namely a student response questionnaire. Based on the results of validity and practicality tests, the statistical module based on the RME approach integrated with Islamic values that has been developed is valid and practical.